Safety issues relating to paraffin usage in Eshane, Kwazulu-Natal - R Matzopoulos; E Jordaan Jordaan; G Carolissen (Journal of Energy in Southern Africa, 2017)
This study describes results of a household survey conducted in Eshane in the rural Kwazulu-Natal Midlands in April 2002, including baseline sociodemographic, energy usage, paraffin-related injury and safety knowledge information. A total of 404 interviews were conducted in five villages that fell within a 10-kilometre radius of the proposed Eshane integrated Energy Centre. Paraffin usage was high (86.6%) and there were no significant differences between electrified and non-electrified villages. Paraffin ingestion by children and paraffin-related fires were reported in 3.6% and 6.3% of households respectively. The majority of respondents had heard safety messages, but message retention was only demonstrated for messages relating to fires, and not ingestion. It seems that safety education may have a role to play in the prevention and response to paraffin-related fires, but that child-resistant packaging may be the only viable intervention for the reduction of ingestion among children.